Emplear bloques nutricionales con adición de subproductos de cosecha (brócoli, panca de maíz y rastrojos de mora), empleados en la alimentación de cuyes machos (Cavia Porcellus) en la fase de crecimiento engorde, en la provincia de Tungurahua, en el cantón Patate, en el sector Tunga. - Salazar Vinueza, Jean Pierre (2020)
In the Tunga sector, Patate Canton, Tungurahua Province, the use of nutritional blocks with the addition of harvest byproducts (broccoli, corn bread, and blackberry stubble), used in the feeding of male guinea pigs (Cavia Porcellus) in the fattening growth phase, was evaluated. Sixty 21 day old male guinea pigs were used, with an average weight of 312.07g, which were distributed under a completely randomized design, with 3 repetitions and 5 animals each, which were housed in individual wooden cubicles for each experimental unit. The study variables (Weight, Weight gain, Feed consumption and Feed conversion), did not register statistical differences (P >0.05) between the treatments averages; however, numerically, the highest final weights were observed in the treatments T0 (alfalfa) and T1 (blackberry stubble) with 1094.86g and 1168.43g, respectively. The highest weight gains in the research were again obtained in T0 (alfalfa) and T1 (blackberry stubble) with 803.21g and 851.36g, respectively. The best yielding feed consumption was shown in T1 (blackberry stubble) and T2 (broccoli waste) with 1194.79g and 1272.57g, respectively. Feed conversion efficiency was shown to be T0 (alfalfa) and T1 (blackberry stubble) with 0.90 and 0.82, respectively. Considering the results, the impact that the use of nutritional blocks with the addition of harvest by-products has on small, medium and large guinea pig producers helps to cover the nutritional requirements in the diet, thus adequately fulfilling the physiological functions necessary for adequate weight gain in the estimated time. Since these wastes are easily accessible and profitable, this will help to save the producers' pockets. The environmental impacts of the use of harvest by-products are generally minimal, since taking advantage of them prevents pests from accumulating when they decompose. In several cases, environmental impacts are invisible to the public, consumers and farmers themselves.